Refining the vulnerability model of low self-esteem and depression Disentangling the effects of genuine self-esteem and narcissism. [article]. - Orth, Ulrich
A growing body of research supports the vulnerability model of low self-esteem and depression, which states that low self-esteem is a risk factor for depression. The goal of the present research was to refine the vulnerability model, by testing whether the self-esteem effect is truly due to a lack of genuine self-esteem or due to a lack of narcissistic self-enhancement. For the analyses, we used data from 6 longitudinal studies consisting of 2,717 individuals. In each study, we tested the prospective effects of self-esteem and narcissism on depression both separately for each construct and mutually controlling the constructs for each other (i.e., a strategy that informs about effects of genuine self-esteem and pure narcissism), and then meta-analytically aggregated the findings. The results indicated that the effect of low self-esteem holds when the narcissism is controlled for (uncontrolled effects = -. 26, controlled effect = -.27). In contrast, the effect of narcissism was close to zero when self-esteem was controlled for (uncontrolled effect = -.06, controlled effect = .01). Moreover, the analyses suggested that the self-esteem effect is linear across the continuum from low to high self-esteem (i.e., the effect was not weaker at very high levels of self-esteem). Finally, self-esteem and narcissism did interact in their effects on depression; that is, individuals with high self-esteem have a lower risk for developing depression, regardless of whether or not they are narcissistic. The findings have significant theoretical implications because they strengthen the vulnerability model of low self-esteem and depression. -- (from the authors)
Keywords: Robins, Richard W; Meier, Laurenz L; Conger, Rand D; Self-esteem.; Narcissism; Depression; Longitudinal; Meta-analysis.